User Interface Designs of an Educational Mobile Application: A Study of Qiraat Teaching and Learning. (3rd May 2021) - Mohd Zaki, Zulkifly; Ishak, Syahidatul Fitriah; Mohamad, Khairul Anuar
Abstract : This paper reports a summative evaluation conducted for the educational mobile application called " Qiraat Sab'ah ." The prototype was developed using the Rapid Application Development (RAD) and User Experience (UX) methodologies. The prototype was improved further based on the formative evaluation feedback gathered from students, lecturers, and the public who wish to learn Qiraat through the mobile application. The summative evaluation was focused on the value and usability of the application if it is being used in a real environment. A total of 50 participants were involved in this evaluation. The result shows that most of the participants provide positive feedback on usability. One of the major highlights from the participants is that the application can be used as a supplementary teaching and learning tool for people who wish to learn Qiraat anytime and anywhere. However, further areas of expansion are needed such as including all chapters ( surahs ) in the Quran and tajweed indicators to the verses before it can be used for real.